Antibacterial transparent nanocomposite material, and preparation method and application thereof
Patent Information
- Application Number
- CN202611355384.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-02
- Publication Date
- 2026-10-09
AI Technical Summary
[0005]本发明的目的是针对背景技术中存在丧失透光性难以实时甄别隐匿活动性出血灶的问题,提出一种抑菌透明的纳米复合材料及其制备方法与应用
[0029]1、本发明制备的纳米复合材料,兼具高透明度、优异延展性、良好力学强度及持久抑菌性,不仅能够用来制备心脏瓣膜,还适用于制备手术中的可视化止血敷料,其透明特性使术者能直接观察覆盖下的组织,实现出血点的实时定位与精准止血,节省手术时间和减少组织损伤风险。
Smart Images

Figure CN122874642A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of nanocomposite materials technology, and in particular to an antibacterial and transparent nanocomposite material, its preparation method, and its application. Background Technology
[0002] In existing technologies, materials such as polyester (PET) and expanded polytetrafluoroethylene (ePTFE) are widely used in the fabrication of long-term implantable devices such as artificial heart valves due to their good biostability and mechanical properties, particularly in fields like cardiovascular surgery. However, these materials are typically white or opaque, and their core design principle is to provide durable mechanical support.
[0003] In all surgical procedures, the effectiveness of wound hemostasis directly determines surgical prognosis and patient safety. Currently, the mainstream hemostatic materials used in clinical practice include gelatin sponges, oxidized regenerated cellulose, and fibrin glue, which can achieve basic hemostasis.
[0004] However, once blood seeps in, the wound quickly loses its translucency, accompanied by swelling and darkening of color. This completely obstructs the surgeon's direct observation of the wound, making it difficult to identify hidden active bleeding foci in real time. This not only prolongs the operation time but also increases the risk of tissue damage. Summary of the Invention
[0005] The purpose of this invention is to address the problem in the prior art where loss of light transmittance makes it difficult to identify hidden active bleeding foci in real time, and to propose an antibacterial and transparent nanocomposite material, its preparation method, and its application.
[0006] In a first aspect, this application provides an antibacterial and transparent nanocomposite material, the raw materials for which are prepared by weight include 80-110 parts of polymer matrix, 3-8 parts of compatibilizer, 2-6 parts of nanoparticles, and 0.1-0.5 parts of antioxidant.
[0007] The polymer matrix includes one or more of thermoplastic polyurethane, polycarbonate, and polyamide;
[0008] The polymer matrix is a thermoplastic transparent resin matrix, using a single resin component or a blend of two or more resins as the main continuous phase structure of the composite material.
[0009] Optionally, the mass ratio of the thermoplastic polyurethane to the polycarbonate is 3:1 to 2:1;
[0010] The thermoplastic polyurethane is a medical-grade transparent polyurethane with a hardness of 85A, an elongation of 400%–500%, and a specific gravity of 1.10–1.14.
[0011] Optionally, the polycarbonate has a density of 1.1–1.3 g / cm³. 3The melt flow rate at 300℃ is 6-8 g / 10 min.
[0012] Optionally, the compatibilizer is an epoxy-functionalized acrylate copolymer with an epoxy equivalent of 270–300 g / mol and a relative molecular mass of 6000–8000.
[0013] Optionally, the nanoparticles have a core-shell structure, with nano-zinc oxide as the core inside, and nano-silica shell and surface functional layer on the outside, forming a three-layer integrated coating structure.
[0014] The nanoparticles are prepared by coating SiO2 onto the surface of ZnO to form a ZnO@SiO2 core-shell structure, and then constructing a surface functional layer on the ZnO@SiO2 surface.
[0015] Optionally, the mass ratio of the polymer matrix, the compatibilizer, and the nanoparticles is (20-35):(1-2):1.
[0016] Secondly, this application provides a method for preparing the antibacterial and transparent nanocomposite material as described in the first aspect, comprising the following steps:
[0017] S1. Preparation of pre-dispersed masterbatch: Mix part of thermoplastic polyurethane, compatibilizer, nanoparticles and part of antioxidant, and melt granulate through a twin-screw extruder to obtain pre-dispersed masterbatch;
[0018] S2. Melt blending: The pre-dispersed masterbatch is mixed with the remaining thermoplastic polyurethane, polycarbonate and the remaining antioxidant, and melt blended by a twin-screw extruder. The melt is then water-cooled, air-dried and pelletized to obtain nanocomposite granules.
[0019] S3. Hot pressing: The nanocomposite material granules are hot pressed to obtain the antibacterial and transparent nanocomposite material.
[0020] Optionally, the portion of thermoplastic polyurethane mentioned in step S1 is 15% to 25% of the total thermoplastic polyurethane.
[0021] The antioxidant portion is 1 / 2 of the total antioxidant amount;
[0022] In step S1, the processing temperature for melt granulation is 150℃~190℃, and the screw speed is 80~150rpm;
[0023] In step S2, the melt blending processing temperature is 190℃~220℃, and the screw speed is 150~350rpm;
[0024] In step S3, the hot pressing temperature is 190℃~220℃, the pressure is 5~15MPa, and the time is 3~10min.
[0025] Thirdly, this application provides an application of the antibacterial and transparent nanocomposite material described in the first aspect in the preparation of medical materials.
[0026] Optionally, the medical material may be a heart valve, an intraoperative visualization hemostatic patch, an absorbable anti-adhesion membrane, or a minimally invasive catheter coating.
[0027] Fourthly, this application provides a medical material, wherein the medical material is a heart valve, an intraoperative visualization hemostatic patch, an absorbable anti-adhesion membrane, or a minimally invasive catheter coating, wherein the medical material is made of an antibacterial transparent nanocomposite material according to the first aspect.
[0028] Compared with the prior art, this application achieves at least one of the following beneficial technical effects:
[0029] 1. The nanocomposite material prepared by this invention has high transparency, excellent ductility, good mechanical strength and long-lasting antibacterial properties. It can not only be used to prepare heart valves, but also to prepare visual hemostatic dressings for surgery. Its transparency allows the surgeon to directly observe the tissue under the dressing, realize real-time positioning of bleeding points and precise hemostasis, save surgical time and reduce the risk of tissue damage.
[0030] 2. This invention, by selecting specific high-elasticity thermoplastic polyurethane and high-rigidity transparent polymer in a specific ratio and introducing specific reactive compatibilizers, can achieve a synergistic improvement in strength and ductility while maintaining the transparency of the material.
[0031] 3. This invention constructs core-shell structured nanoparticles with nano-zinc oxide as the antibacterial core, dense silica as the intermediate shell, and epoxy silane as the surface functional layer. This enables the material to have highly efficient and long-lasting antibacterial properties with extremely low addition amounts, without compromising its transparency and mechanical properties.
[0032] 4. This invention improves the overall performance of nanomaterials by using a compatibilizer with epoxy functional groups and core-shell nanoparticles with epoxy groups on the surface, and blending them with thermoplastic polyurethane and polycarbonate matrices with active groups at the ends. Attached Figure Description
[0033] Figure 1 This is a schematic diagram of the separation state of a heart valve made of nanomaterials.
[0034] Figure 2 A schematic diagram of the forming state of a nanomaterial heart valve structure; Detailed Implementation
[0035] The following specific examples illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and various details in this specification can also be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that, unless otherwise specified, the following embodiments and features described therein can be combined with each other.
[0036] The thermoplastic polyurethane is a medical-grade transparent polyurethane with a hardness of 85A, an elongation of 400%–500%, and a specific gravity of 1.10–1.14. It is from Lubrizol, Tecothane® thermoplastic polyurethane, TT~1085A.
[0037] The polycarbonate has a density of 1.1–1.3 g / cm³ and a melt flow rate of 6–8 g / 10 min at 300 °C. It is from Covestro and is polycarbonate Makrolon® RX1805.
[0038] The epoxy-functionalized acrylate copolymer, with an epoxy equivalent of 270–300 g / mol and a relative molecular mass of 6000–8000, is from BASF, specifically JoncrylADR4368C. The ZnO particle size is 20–40 nm and is from Aladdin.
[0039] Example 1
[0040] This embodiment provides an antibacterial and transparent nanocomposite material, the raw materials for which, by weight, include 95 parts of polymer matrix, 5 parts of compatibilizer, 4 parts of nanoparticles, and 0.3 parts of antioxidant.
[0041] The polymer matrix is thermoplastic polyurethane and polycarbonate in a mass ratio of 2.5:1, and the compatibilizer is an epoxy-functionalized acrylate copolymer. The nanoparticles have a core-shell structure, with nano-zinc oxide as the core, and an outer shell of nano-silica and a surface functional layer.
[0042] The preparation method of the nanoparticles includes the following steps:
[0043] A1. Coating ZnO with SiO2 to obtain ZnO@SiO2;
[0044] A2. Construct a surface functional layer on the ZnO@SiO2 surface to obtain the desired result.
[0045] The specific steps of step A1 are as follows: ZnO is ultrasonically dispersed in an ethanol-water solution, ammonia is added, the mixture is heated and stirred while TEOS is slowly added dropwise, and the reaction is maintained at this temperature for 10 hours. After centrifugation, the supernatant is discarded, and the mixture is washed three times alternately with ethanol and deionized water, followed by vacuum drying to obtain ZnO@SiO2. The solid-liquid ratio of ZnO to the ethanol-water solution is 1 g: 150 mL.
[0046] In this embodiment, the volume fraction of ethanol in the aqueous ethanol solution is 90%.
[0047] In this embodiment, the specific conditions for ultrasonic dispersion are the same: power is 300W and time is 30min.
[0048] The specific conditions for heating and stirring are: temperature 38℃ and stirring speed 350rpm.
[0049] The ratio of ZnO, ammonia, and TEOS is 1g:1.5mL:0.8g.
[0050] By constructing core-shell structured nanoparticles with nano-zinc oxide as the antibacterial core, silica as the intermediate shell, and epoxy silane as the surface functional layer, highly efficient and long-lasting antibacterial properties can be imparted to the material at extremely low addition levels, with almost no impairment to its transparency and mechanical properties. This is because the intermediate silica shell acts as a refractive index transition layer, buffering the high refractive index of the nano-zinc oxide core to near that of the polymer matrix, greatly reducing light scattering between the filler and the matrix. Simultaneously, the epoxy groups on the surface can chemically react with the polymer matrix during processing, allowing the nanoparticles to be firmly anchored in the matrix through covalent bonds, achieving uniform nanoscale dispersion and avoiding performance degradation due to agglomeration. Furthermore, the silica shell also plays a role in the slow-release control of zinc ion release from the nano-zinc oxide, extending the antibacterial period and improving biocompatibility.
[0051] In this invention, the specific conditions for vacuum drying are all the same: the temperature is 60°C and the time is 12 hours.
[0052] In step A2, the surface functional layer is constructed as follows: ZnO@SiO2 is ultrasonically dispersed in an ethanol aqueous solution, the pH of the system is adjusted to 5, (3-glycidyl ether oxypropyl)trimethoxysilane is added, the mixture is heated and stirred, the supernatant is discarded by centrifugation, and the mixture is washed three times alternately with ethanol and deionized water and then vacuum dried.
[0053] The solid-liquid ratio of ZnO@SiO2 and the aqueous ethanol solution is 1g:250mL.
[0054] The solid-liquid ratio of ZnO@SiO2 and (3-glycidyl ether oxypropyl)trimethoxysilane is 1 g: 1.5 mL.
[0055] The specific conditions for the heating and stirring reaction are: temperature 55℃, stirring speed 350rpm, and time 7h.
[0056] The mass ratio of the polymer matrix, compatibilizer, and nanoparticles is 95:5:4.
[0057] The antioxidants are antioxidant 1010 and antioxidant 168 in a mass ratio of 2:1.
[0058] By employing a compatibilizer with epoxy functional groups and core-shell nanoparticles with epoxy groups on their surface, and blending them with TPU and PC matrices containing active groups at the ends, the overall performance of the nanomaterials was significantly improved. This is because, during the melt blending process, the compatibilizer molecules act as multifunctional bridges, reacting at one end with the epoxy groups on the nanoparticle surface and at the other end with the amino / hydroxyl groups of TPU or the terminal hydroxyl groups of PC. This creates an in-situ three-dimensional chemical cross-linked network spanning both micro and macro scales between the nanofiller and the polymer, and between the TPU and PC phases. This chemically enhanced interface greatly improves stress transfer efficiency, enhances the mechanical strength and toughness of the material, and fundamentally stabilizes the nano-dispersion state and phase morphology, resulting in high-performance materials.
[0059] A method for preparing an antibacterial and transparent nanocomposite material, applied to the aforementioned nanocomposite material, comprises the following steps:
[0060] S1. Preparation of pre-dispersed masterbatch: Mix 20% thermoplastic polyurethane, compatibilizer, nanoparticles, and half of the antioxidant, and melt granulate using a twin-screw extruder to obtain pre-dispersed masterbatch;
[0061] S2. Melt blending: The pre-dispersed masterbatch is mixed with the remaining thermoplastic polyurethane, polycarbonate and antioxidant, and melt blended using a twin-screw extruder. The melt is then cooled with water, air-dried and pelletized to obtain nanocomposite granules.
[0062] S3. Hot pressing: The nanocomposite material granules are hot pressed into shape to obtain the final product.
[0063] In step S1, the process parameters for melt granulation are: zone 1 160℃, zone 2 170℃, zone 3 175℃, die head 180℃; screw speed 100rpm.
[0064] In step S2, the process parameters for melt blending are: zone 1 190℃, zone 2 200℃, zone 3 205℃, zone 4 210℃, die head 210℃; screw speed is 250 rpm.
[0065] In step S3, the specific conditions for hot pressing are: temperature 205℃, pressure 8MPa, and time 5min.
[0066] Example 2
[0067] This embodiment provides an antibacterial and transparent nanocomposite material. The specific implementation method is the same as that in Embodiment 1, except that the raw materials for its preparation, by weight, include 99 parts of polymer matrix, 6 parts of compatibilizer, 3 parts of nanoparticles, and 0.3 parts of antioxidant.
[0068] The mass ratio of the polymer matrix, compatibilizer, and nanoparticles is 33:2:1.
[0069] Comparative Example 1
[0070] This comparative example provides an antibacterial and transparent nanocomposite material. The specific implementation method is the same as that in Example 1, except that the thermoplastic polyurethane has a hardness of 64D, an elongation of 300%, and a specific gravity of 1.18. It is from Lubrizol, Tecothane® thermoplastic polyurethane, TT~1065D.
[0071] Comparative Example 2
[0072] This comparative example provides an antibacterial and transparent nanocomposite material. The specific implementation method is the same as that in Example 1, except that the polymer matrix is thermoplastic polyurethane and polycarbonate TG (polyethylene terephthalate ~ 1,4 ~ cyclohexanediol ester) in a mass ratio of 2.5:1.
[0073] The density of the polycarbonate TG is 1.8 g / cm³. 3 Shrinkage rate is 0.005~0.007mm / mm, from Eastman, MX711.
[0074] Comparative Example 3
[0075] This comparative example provides an antibacterial and transparent nanocomposite material. The specific implementation method is the same as that in Example 1, except that the polymer matrix is thermoplastic polyurethane and polycarbonate in a mass ratio of 1:1.
[0076] Comparative Example 4
[0077] This comparative example provides an antibacterial and transparent nanocomposite material. The specific implementation method is the same as that in Example 1, except that the polymer matrix is thermoplastic polyurethane and polycarbonate in a mass ratio of 4:1.
[0078] Comparative Example 5
[0079] This comparative example provides an antibacterial and transparent nanocomposite material. The specific implementation method is the same as that in Example 1, except that the compatibilizer is an epoxy-functionalized acrylate copolymer with an epoxy equivalent of 485 g / mol and a relative molecular mass of 7100, which is from BASF, Joncryl ADR4400.
[0080] Comparative Example 6
[0081] This comparative example provides an antibacterial and transparent nanocomposite material. The specific implementation method is the same as that in Example 1, except that the compatibilizer is maleic anhydride grafted POE, from DuPont, Fusabond N493.
[0082] Comparative Example 7
[0083] This comparative example provides an antibacterial and transparent nanocomposite material. The specific implementation method is the same as that in Example 1, except that the ratio of ZnO, ammonia and TEOS is 1g:1.5mL:2g.
[0084] Comparative Example 8
[0085] This comparative example provides an antibacterial and transparent nanocomposite material. The specific implementation method is the same as that in Example 1, except that in step A2, the surface functional layer is constructed as follows: ZnO@SiO2 is ultrasonically dispersed in an ethanol aqueous solution, the pH of the system is adjusted to 5, 3-aminopropyltriethoxysilane is added, the mixture is heated and stirred, the supernatant is discarded by centrifugation, and the mixture is washed three times alternately with ethanol and deionized water and then vacuum dried.
[0086] Comparative Example 9
[0087] This comparative example provides an antibacterial and transparent nanocomposite material. The specific implementation method is the same as that in Example 1, except that the raw materials for preparing the antibacterial and transparent nanocomposite material, by weight, include 95 parts of polymer matrix, 5 parts of compatibilizer, 10 parts of nanoparticles, and 0.3 parts of antioxidant.
[0088] The mass ratio of the polymer matrix, compatibilizer, and nanoparticles is 9.5:3:2.
[0089] Comparative Example 10
[0090] This comparative example provides an antibacterial and transparent nanocomposite material. The specific implementation method is the same as that in Example 1, except that the raw materials for preparing the antibacterial and transparent nanocomposite material, by weight, include 95 parts of polymer matrix, 1 part of compatibilizer, 4 parts of nanoparticles, and 0.3 parts of antioxidant.
[0091] The mass ratio of the polymer matrix, compatibilizer, and nanoparticles is 95:1:4.
[0092] Performance Testing: The tensile strength and elongation at break of the nanocomposite materials were tested according to GB / T1040.3-2006. The light transmittance of the nanocomposite materials was tested according to GB / T2410-2008. The antibacterial rate of the nanocomposite materials was tested according to GB / T31402-2015, using Staphylococcus aureus (ATCC6538) as the bacterial strain, with a contact time of 24 hours. The biocompatibility of the nanocomposite materials was tested according to ISO10993-5:2009, through in vitro cytotoxicity testing, measuring the relative cell proliferation rate (RGR). RGR ≥ 100% was grade 0; 75%~99% was grade 1; 50%~74% was grade 2; 25%~49% was grade 3; 1%~24% was grade 4; and 0 was grade 5. Medical devices typically require grade ≤ 1. The results are shown in the table below.
[0093]
[0094] As shown in the table above, the nanocomposites prepared in Examples 1 and 2 exhibit excellent mechanical properties, high transparency, good ductility, and also possess durable antibacterial properties and excellent biocompatibility, making them suitable for application in the field of medical materials technology. Comparative Example 1 used polyurethane with high hardness; Comparative Example 2 replaced polycarbonate with polycarbonate TG; Comparative Example 3 used excessive polycarbonate; Comparative Example 4 used excessive polyurethane; Comparative Example 5 had an excessively high epoxy equivalent compatibilizer; Comparative Example 6 used a non-reactive compatibilizer with poor compatibilization effect; Comparative Example 7 used excessive TEOS, resulting in an excessively thick SiO2 shell; Comparative Example 8 used aminosilane for the surface functional layer; Comparative Example 9 used excessive nanoparticles; and Comparative Example 10 had insufficient compatibilizer. The nanocomposites prepared in these examples all showed varying degrees of performance degradation compared to those in Example 1.
[0095] In summary, this invention successfully prepared a nanocomposite material with high transparency, excellent ductility, good mechanical strength, and long-lasting antibacterial properties by preparing specific nanoparticles and using specific polymer matrices and compatibilizers. It also has excellent biocompatibility and low toxicity, making it applicable to the field of medical materials. It can be used not only to prepare heart valves but also to prepare visual hemostatic dressings for surgery. Its transparency allows surgeons to directly observe the tissue under the dressing, enabling real-time location and precise hemostasis of bleeding points.
[0096] Applications of an antibacterial and transparent nanocomposite material in the field of medical materials technology, such as... Figure 1 and Figure 2 As shown, the nanocomposite material can be used to prepare heart valves. In addition, the nanocomposite material can be used to prepare intraoperative visualization hemostatic patches, absorbable anti-adhesion membranes, and minimally invasive catheter coatings, solving the technical problem that the opacity of existing polyester and polytetrafluoroethylene materials makes it difficult to detect postoperative bleeding points in a timely manner.
[0097] Nanocomposite materials are ideal building blocks for next-generation artificial heart valves. By combining nanofillers (such as nano-hydroxyapatite, carbon nanotubes, and nano-silica) with polyurethane, multi-level micro / nano structures are constructed. By controlling the elastic modulus, tensile strength, and elongation at break, the defects of traditional artificial valve materials—either being too stiff or lacking elasticity—are eliminated, and their mechanical compliance closely resembles that of natural human valve leaflets. Simultaneously, they improve resistance to repeated bending fatigue, adapting to the dynamic load of the heart's cyclical opening and closing every minute, delaying leaflet tearing and creep deformation under long-term pulsation, and extending valve lifespan.
[0098] Artificial heart valves mainly consist of four core parts: annular valve base, leaflet assembly, fixation sleeve, and fluid interface. The valve base is a cylindrical annular base with fluid conduits extending outward from the side wall to serve as blood inlet and outlet channels. The upper part of the base forms an annular support end face to support the leaflet assembly, forming the main body of the blood flow channel, which is suitable for implantation and installation of cardiovascular tubing.
[0099] The leaflet assembly consists of symmetrically arranged leaflet structures mounted on the inner side of the base. It is a bileaf valve configuration, with the roots of the two leaflets fixed to the annular support area. The free ends of the leaflets converge towards the center. When the heart contracts and the forward blood flow impacts, the leaflets open inward, forming a flow channel in the center, allowing blood to pass smoothly. When the heart relaxes and blood tends to flow backward, the leaflets close together, blocking the reverse blood flow and achieving unidirectional conduction, simulating the unidirectional flow control function of a natural heart valve.
[0100] After assembly, the fastening sleeve covers the upper outer edge of the valve body, limiting and fixing the leaflet assembly on the base, constraining the assembly position of the leaflet root, and preventing the leaflet from loosening or shifting during pulsation; the sleeve provides uniform circumferential constraint force, ensuring the long-term stability of the leaflet hinge position and maintaining the opening and closing trajectory unchanged.
[0101] The valve body base is an integral cylindrical pressure-bearing shell, with the side wall extending outward to form a fluid interface; the fluid interface is a straight tubular channel, serving as a connection port for blood to enter and exit the valve cavity.
[0102] Nanocomposite materials possess both the strong and robust mechanical properties of heart valve materials and high transparency. Applying them to surgical wound hemostasis can address clinical challenges in the aforementioned techniques. Their transparency allows surgeons to clearly visualize the wound after covering or suturing, enabling rapid detection and treatment of any new bleeding points, thus achieving precise hemostasis and improving surgical safety and efficiency.
[0103] The visual hemostatic patch uses nanofibers to construct a porous surface structure, which captures and aggregates blood cells and platelets. Inside, chitosan and polydopamine nanocomponents synergistically activate platelets, promote fibrin cross-linking, and shorten clotting time.
[0104] The nanocarrier loads a blood-specific response probe. When active bleeding occurs in the wound, the blood penetrates the contact layer and reaches the indicator layer, triggering a stepwise color change. The base color represents no exudation, the light color represents a small amount of bleeding, and the obvious color represents continuous active bleeding.
[0105] The above specific embodiments are merely several optional embodiments of the present invention. Based on the technical solutions of the present invention and the relevant teachings of the above embodiments, those skilled in the art can make various alternative improvements and combinations to the above specific embodiments.
Claims
1. A transparent, antibacterial nanocomposite material, characterized in that, The raw materials for its preparation, by weight, include 80-110 parts of polymer matrix, 3-8 parts of compatibilizer, 2-6 parts of nanoparticles, and 0.1-0.5 parts of antioxidant; The polymer matrix includes one or more of thermoplastic polyurethane, polycarbonate, and polyamide; The polymer matrix is a thermoplastic transparent resin matrix, using a single resin component or a blend of two or more resins as the main continuous phase structure of the composite material.
2. The antibacterial transparent nanocomposite material according to claim 1, characterized in that, The mass ratio of the thermoplastic polyurethane to the polycarbonate is 3:1 to 2:1; The thermoplastic polyurethane is a medical-grade transparent polyurethane with a hardness of 85A, an elongation of 400%–500%, and a specific gravity of 1.10–1.
14.
3. The antibacterial transparent nanocomposite material according to claim 2, characterized in that, The polycarbonate has a density of 1.1–1.3 g / cm³. 3 The melt flow rate at 300℃ is 6-8 g / 10 min.
4. The antibacterial transparent nanocomposite material according to claim 1, characterized in that, The compatibilizer is an epoxy-functionalized acrylate copolymer with an epoxy equivalent of 270–300 g / mol and a relative molecular mass of 6000–8000.
5. The antibacterial transparent nanocomposite material according to claim 1, characterized in that, The nanoparticles have a core-shell structure, with nano zinc oxide inside and nano silica shell and surface functional layer on the outside, forming a three-layer integrated coating structure. The nanoparticles are prepared by coating SiO2 onto the surface of ZnO to form a ZnO@SiO2 core-shell structure, and then constructing a surface functional layer on the ZnO@SiO2 surface.
6. The antibacterial transparent nanocomposite material according to claim 1, characterized in that, The mass ratio of the polymer matrix, the compatibilizer, and the nanoparticles is (20-35):(1-2):
1.
7. A method for preparing an antibacterial transparent nanocomposite material as described in any one of claims 1 to 6, characterized in that, Includes the following steps: S1. Preparation of pre-dispersed masterbatch: Mix part of thermoplastic polyurethane, compatibilizer, nanoparticles and part of antioxidant, and melt granulate through a twin-screw extruder to obtain pre-dispersed masterbatch; S2. Melt blending: The pre-dispersed masterbatch is mixed with the remaining thermoplastic polyurethane, polycarbonate and the remaining antioxidant, and melt blended by a twin-screw extruder. The melt is then water-cooled, air-dried and pelletized to obtain nanocomposite granules. S3. Hot pressing: The nanocomposite material granules are hot pressed to obtain the antibacterial and transparent nanocomposite material.
8. The method for preparing an antibacterial and transparent nanocomposite material according to claim 7, characterized in that, The portion of thermoplastic polyurethane mentioned in step S1 is 15% to 25% of the total amount of thermoplastic polyurethane; The antioxidant portion is 1 / 2 of the total antioxidant amount; In step S1, the processing temperature for melt granulation is 150℃~190℃, and the screw speed is 80~150rpm; In step S2, the melt blending processing temperature is 190℃~220℃, and the screw speed is 150~350rpm; In step S3, the hot pressing temperature is 190℃~220℃, the pressure is 5~15MPa, and the time is 3~10min.
9. The application of an antibacterial transparent nanocomposite material according to any one of claims 1 to 6 in the preparation of medical materials, wherein the medical material is a heart valve, an intraoperative visualization hemostatic patch, an absorbable anti-adhesion membrane, or a coating for a minimally invasive catheter.
10. A medical material, wherein the medical material is a heart valve, an intraoperative visualization hemostatic patch, an absorbable anti-adhesion membrane, or a minimally invasive catheter coating, wherein the medical material is made of an antibacterial transparent nanocomposite material according to any one of claims 1 to 6.